Parental alienation: when parents and children need help - Marta Filipa Mendonça Gomes (Instituto Politécnico de Viseu, 2016)
The social changes that are contributing to modifications in family structure are also, among others, associated with an increase in divorces and difficulties in parenting. In this context, there are specific problems that arise such as parental alienation, where one of the parents, through manipulative strategies and maneuvers, tries to tarnish the image of the other, seeking to exclude him of child's life, destroying their bonding. Often, these actions can turn on false allegations of child abuse. For this reason it becomes even more important raising awareness on this issue. This article will focus the concept of parental alienation, as well as its causes, manifestations and effects that are associated with their practice.